The Effect of Pliometric Training and Tabata Training on the T Kick Ability of Pencak Silat Walet Puti Extracurricular Students - Elsa Rahma, Yani; Putra, Muarif Arhas; Manurizal, Lolia (Indonesian Journal of Sport Management, 2024)
This study was conducted to determine the effect of pliometric training and tabata training on the ability of T-kicks of pencak silat walet puti extracurricular students of SMP N 1 Ujungbatu. The method used in this research is experimental. Data collection was carried out using experiments using normality tests with the liliefors method to determine the effect of pliometric training and tabata training on the ability of Walet Puti Pencak Silat Extracurricular T-Kick at SMP N 1 Ujungbatu. Data testing in this study using the normality test with the liliefors method, with the acquisition of the value Tcount = 19.082 for pliometric training and Ttable = 22.002 for tabata training with the test results tcount (0.216) < ttable (1.833) where it can be concluded that the tabata training method is more effective than pliometric training.